Smrtne žrtve Maribora v času druge svetovne vojne in neposredno po njej - Rendla, Marta (Studia Historica Slovenica, 2025)
In their contribution, the authors present the loss of human life suffered by the city of Maribor during and immediately after World War II. The analysis of the casualties is based on the research database titled Fatalities among the Population in the Territory of the Republic of Slovenia During and Immediately after World War II. In the first part, the fatalities in Maribor are presented comparatively, both in the context of the entire Slovenian territory and in the provincial context. In the second part, the fatalities are analysed according to the year of death, military status, cause of death, perpetrator of death, and country of death. In the third part, the authors focus on the underage fatalities with the right of domicile in Maribor at the beginning of World War II. They examine their social and military status or their wartime role, as well as the cause, year, country, and perpetrator of their deaths. In the final part, the consequences of the war in individual provinces are also presented from the demographic point of view. This article on the loss of human life contributes to a more comprehensive victimological picture of the city of Maribor.
Keywords: druga svetovna vojna; Maribor; podatkove baze; smrtne žrtve; zgodovina